(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Willard K, Aipassa MI, Sardjono MA, Rujehan, Ruslim Y, Kristiningrum R. 2022. Locating the unique biodiversity of Balikpapan Bay as an ecotourism attraction in East Kalimantan, Indonesia. Biodiversitas 23: 2342-2357. Balikpapan Bay is rich in biodiversity and natural beauty that present unique opportunities for the developing ecotourism industry in East Kalimantan, Indonesia. This study aimed to identify biodiversity hotspots with potential as ecotourism attractions. Four field surveys by boat, each survey taking between 10 to 22 hours duration, tracked the river and tidal flow through the Bay, recording highlights of biodiversity at 19 defined observation points. The study results recorded observations on five species listed in the IUCN protected species classification, namely: Lesser Adjutant Stork (Leptoptilos javanicus) - classified as a Vulnerable species; Proboscis Monkey (Nasalis larvatus), Irrawaddy Dolphin (Orcaella brevirostris) and Green Turtle (Chelonia mydas) - classified as Endangered species; and the Hawksbill Turtle (Eretmochelys imbricata) - classified as Critically Endangered. In addition, details were recorded of a unique variant of the mangrove species Rhizophora apiculata, with leaves that have a vibrant yellow color instead of the usual green. Combined with great views, including at night when there are enchanting displays of Fireflies (Lampyridae) on several riverbanks, the biodiversity of the waterways results in Balikpapan Bay having great potential as an ecotourism destination. Therefore, this study provides useful input to relevant agencies charged with responsibility for conserving and managing the natural resources of the Bay for the benefit of communities who stand to gain economically from developing this ecotourism potential.